Dissolved major element (Ca, Sr, Mg, K, Li) concentration data of the western Atlantic Ocean meridional section GA02 (GEOTRACES) and Arctic Ocean cruise JR271 (BODC) - Edel Mary O extquotesingleSullivan; Zvi Steiner (PANGAEA, 2025)
This dataset presents salinity-normalized dissolved major element (Ca, Mg, K, Sr, Li) concentrations in the western Atlantic Ocean and the Arctic Ocean. Atlantic samples were collected along the western meridional GEOTRACES section GA02 comprised of cruises JR057 (Punta Arenas (Chile) 02-03-2011 to Las Palmas (Spain) 06-04-2011 ), PE321 (Bermuda 11-06-2010 to Fortaleza (Brazil) 08-07-2010), PE319 (Scrabster 28-04-2010 to Bermuda 25-05-2010), and PE358 (Reykjavik (Iceland) 29-07-2012 to Texel (Netherlands) 19-08-2012). Samples for dissolved major ions were sub-sampled from trace metal sample collection stored at the Royal Netherlands Institute for Sea Research (NIOZ). Samples for the Arctic Ocean were collected on BODC cruise JR271 (Immingham 01-06-2012 to Reykjavik 02-07-2012). Samples were analysed for Na, Ca, Mg, K, Li and Sr using a Varian-720 ES ICP-OES. Samples were diluted by a factor of 78-82 in 0.12 M HCl to the same final salinity. Multiple spectral lines were selected for each element, and samples were corrected for instrumental drift by sample-standard bracketing with IAPSO P157 diluted to the same final salinity. Calibration was performed on 7 dilutions of IAPSO P157. Element-to-sodium ratios were calculated for all combinations of spectral lines. Assuming a constant Na-to-salinity (PSU)=35 ratio, the element/Na ratios were multiplied by 0.46847 μmol kg-1 to obtain the salinity (PSU)-normalized element concentration, and by the ratio of practical to absolute salinity (TEOS-10). The TEOS-10 absolute salinities were calculated from EOS-80 values using the Gibb extquotesingles Oceanographic Toolbox using the R package extquotesinglegsw extquotesingle (v 1.1-1).